Adipose Factor ANGPTL4: Its Role in Aging Mechanisms and Associated Diseases - Wang X; Chang HC; Gu X; Zhang Y; Bao Z (Clinical Interventions in Aging)
Xiaojun Wang,1,2,* Hung-chen Chang,1,2,* Xuchao Gu,1,2,* Yuxin Zhang,1,2 Zhijun Bao1– 3 1Shanghai Key Laboratory of Clinical Geriatric Medicine, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China; 2Shanghai Institute of Geriatric Medicine, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China; 3Department of Gerontology, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhijun Bao; Yuxin Zhang, Shanghai Key Laboratory of Clinical Geriatric Medicine, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People’s Republic of China, Email zhijunbao@fudan.edu.cn; 13598792767@163.comAbstract: The angiopoietin-like protein 4 (ANGPTL4), also known as fasting-induced adipose factor, is a secreted glycoprotein that belongs to the ANGPTL protein family. Due to its expression in various cell types and tissues and its interactions with other proteins, ANGPTL4 plays diverse roles within its family, exhibiting a wider range of molecular functions. For instance, ANGPTL4 is intricately involved in modulating central energy metabolism and enhancing exercise endurance, while also acting as a pivotal mediator in the interaction between gut microbiota and host lipid metabolism. Moreover, the expression of ANGPTL4 is directly controlled by aging-related signaling pathways. Its excessive activation accelerates the aging process by triggering mechanisms like heightened oxidative stress, epithelial-mesenchymal transition (EMT) and fibrosis, abnormal lipid accumulation, and cellular arrest, thereby advancing the development of age-related diseases. Given the pivotal roles of ANGPTL4 and its associated molecules in organ fibrosis and cancer advancement, targeting ANGPTL4 emerges as a promising therapeutic approach. However, the intricate and sometimes conflicting functions of the two cleavage fragments of ANGPTL4, namely N-terminal fragment (nANGPTL4) and C-terminal fragment (cANGPTL4), in different chronic diseases—exerting inhibitory or stimulatory effects depending on the disease stage—have posed challenges to the progress of ANGPTL4 antibody therapy. This review provides an overview of the biological mechanisms of ANGPTL4, its dual impact on fibrosis and tumorigenesis, and highlights its recent advancements as a potential biomarker in age-related diseases and inflammation-related conditions. ANGPTL4 is a high-potential but complex target, requiring mechanism-driven strategies for safe clinical translation.Keywords: ANGPTL4, adipose factor, age-related diseases, mechanism